OUTCOMES OF PATIENTS WITH EXUDATIVE AGE-RELATED MACULAR DEGENERATION TREATED WITH ANTIVASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY FOR THREE OR MORE YEARS: A Review of Current Outcomes. Issue 8 (August 2018) - Qin, Vivian L.; Young, Jason; Silva, Fabiana Q.; Conti, Felipe F.; Singh, Rishi P.
Abstract : Purpose: To summarize the findings of long-term outcomes of anti-vascular endothelial growth factor (VEGF) therapy (≥36 months) in patients with exudative age-related macular degeneration. Methods: Studies reporting long-term outcomes (≥36 months) of anti-VEGF therapy (n = 11) were identified and analyzed for changes in visual acuity (VA), optical coherence tomography, and safety findings. Results: Six prospective extension studies of Phase 3 clinical trials and five retrospective evaluation studies were identified. The largest improvements in VA with anti-VEGF treatment were found in Years 1 to 2 after treatment initiation. In five studies, VA ultimately declined below patients' pretreatment initial baseline; in three studies, VA ultimately returned to patients' baseline; in three studies, VA decreased but ultimately remained improved over patients' baseline. There was a trend demonstrating that a higher frequency of intravitreous injections showed a better maintenance in VA. Rates of adverse events were similar to previous registration studies of anti-VEGF drugs. Conclusion: The body of evidence to date regarding long-term anti-VEGF treatment indicates a variable course at greater than 36 months follow-up and seems to be dependent on the treatment protocol. Consistent dosing with fluid-free interval is suggested to maintain VA gains in patients with exudative age-related macular degeneration. There is no evidence suggesting that there are additional adverse events from long-term anti-VEGF use. Abstract : Based on data from extension studies of Phase 3 clinical trials and retrospective studies greater than 36 months, patients with exudative age-related macular degeneration treated with intravitreous injections of anti-vascular endothelial growth factor agents for 3 or more years have a variable course dependent on the treatment protocol used.